RELASI ANTAR UMAT MAYORITAS DAN MINORITAS: STUDI MASYARAKAT TIONGHOA DI SURABAYA - Wasisto Raharjo Jati (Harmoni, 2021)
This study aims to analyse the relationship problem between majoritarian and minorities within Indonesian society. More specifically, relationship between Chinese-Indonesians, which are minorities and majoritarian in both religion and ethnicity. By using mixed method such as case study that conducted in two locations Surabaya and Pangkalpinang, archival research, and also focused group discussion that done in less than a year, this study reveals some interesting findings. The first finding shows both linguistic and social integration between Chinese-Indonesians and majoritarian causing social acceptance to the minorities. This particularly refers to the use of “Bahasa Jawa” (Javanese language) is the key to integrate Chinese – Indonesians and majoritarian in Surabaya. This first finding also shows the fluid relationship between minorities and majoritarian albeit both parties still to defend their hereditary identities. The theoretical framework itself is state politics to frame state’s attitude in regulating society. Conclusion of the study is the long existence of Chinese-Indonesians as one of minorities enable them to get wide social acceptance from majoritarian society. This condition subsequently affects state politics to be more accommodative when it comes to regulate minorities and majorities.